Interventional ultrasound in obstetrics, gynaecology and the breast - Santolaya-Forgas, Joaquin; Lémery, Didier (Blackwell Science, 1998)
This specialized volume offers an in-depth overview of interventional ultrasound techniques across obstetrics, gynecology, and breast medicine. Section 1 focuses on fetal medicine, encompassing counseling, legal considerations, and a wide range of ultrasound-guided diagnostic and therapeutic procedures, including chorionic villus sampling, fetal transfusions, and interventions in multifetal pregnancies. Section 2 addresses interventional ultrasound applications in gynecology, from adnexal mass management to assisted reproduction and urogynecology. Section 3 explores the role of ultrasound in breast interventions, highlighting techniques for lesion localization and biopsy. This multidisciplinary work serves as a comprehensive reference for clinicians involved in minimally invasive procedures in women’s health.